Improved MRAS observer with rotor flux correction terms and FLC-based adaptive law for sensorless induction motor drives - Mohamed S. Zaky; Mohamed K. Metwaly (Scientific Reports)
Abstract This paper presents an improved model reference adaptive system (MRAS) speed observer for sensorless induction motor drives (SIMDs) with rotor flux correction terms. Instead of relying only on the rotor flux estimate, which has issues with pure integration at low speeds, the suggested MRAS observer employs the dq stator currents and their estimation errors in the adjustable model of the IM. The rotor flux dynamics are considered correction terms for the estimated stator current to update and improve the estimated speed’s accuracy. The adaptation process uses a fuzzy logic controller (FLC) rather than a traditional PI controller to enhance the robustness of the suggested technique. A DSP-DS1103-based laboratory prototype is used to evaluate the proposed stator current-based MRAS observer with FLC for indirect field-oriented control (IFOC) of SIMDs. The simulations are executed using Matlab/Simulink. Additionally, a comparison is made between the performance of the suggested and traditional MRAS schemes. The tests demonstrate the accuracy and robustness of the improved MRAS observer in four quadrant modes of operation, especially at very low and zero speeds.